The Earthworm Eisenia fetida Can Help Desalinate a Coastal Saline Soil in Tianjin, North China. - Tao Zhang; Suyan Li; Xiangyang Sun; Yang Zhang; Xiaoqiang Gong; Ying Fu; Liming Jia (PLoS ONE)
A laboratory microcosm experiment was conducted to determine whether the earthworm Eisenia fetida could survive in a saline soil from a field site in North China, and an experiment using response surface methodology was conducted at that field site to quantify the effects of E. fetida and green waste compost (GWC) on the salt content of the soil. The microcosm results showed that E. fetida survived in GWC-amended saline soil and increased the contents of humic acid, available N, and available P in the GWC-amended soil. The data from the field experiment were described by the following second-order model: [Formula in text], where y is the decrease in soil salinity (g of salt per kg of dry soil) relative to the untreated control, x1 is the number of E. fetida added per m2, and x2 is the quantity of GWC added in kg per m2. The model predicted that the total salt content of the saline soil would decrease by > 2 g kg(-1) (p<0.05) when 29-90 individuals m-2 of E. fetida and 6.1-15.0 kg m(-2) of GWC were applied. We conclude that the use of E. fetida for soil desalination is promising and warrants additional investigation.